Prognostic value of P-selectin and sST2 in patients with multiple myeloma - M. O. Panasenko; B. B. Samura; S. Ya. Dotsenko (Zaporozhye State Medical University, 2022)
Cardiac involvement is one of the most important prognostic markers in multiple myeloma. However, prognostic value of novel biomarkers, such as soluble suppression of tumorigenicity 2 (sST2), P-selectin is unknown in multiple myeloma. The aim of the work was to investigate the additive predictive effects of novel biomarkers P-selectin and sST2 for cardiovascular events of multiple myeloma patients. Materials and methods. Levels of P-selectin and sST2 were after anticancer treatment in a total of 67 multiple myeloma patients. The median follow-up duration of the censored cases was 14.0 (11.4-19.1) months. A total of 4 deaths occurred during the follow-up period. ELISA method for measurements of circulating level of P-selectin and sST2 was used. Results. During follow-up, 36 cardiovascular events and 2 deaths unrelated to cardiovascular events were recorded in 18 (26.9 %) patients. During the study, patients were hospitalized 10 times due to cardiovascular disease. At baseline patients with MM and cardiovascular events which appeared during the observation period had higher levels of P-selectin (P < 0.01), sST2 (P = 0,018), compared to patients without cardiovascular events. Two novel biomarkers, P-selectin and sST2 showed satisfactory predictive performances for one-year cardiovascular events from ROC analysis. Best cut-off values for predicting one-year cardiovascular events were selected (for sST2 - 31.05 ng/ml, with a sensitivity of 71.5 % and a specificity of 89.8 %; for P-selectin - 54.21 ng/ml, with a sensitivity of 69.6 % and a specificity of 86.2 %). The combination of biomarkers had better prognostic properties compared to P-selectin. Conclusions. In patients with confirmed multiple myeloma, the biomarkers P-selectin and sST2 showed significant prognostic properties in the occurrence of cardiovascular events during 1 year of follow-up.